Leaf plasticity across wet and dry seasons in Croton blanchetianus (Euphorbiaceae) at a tropical dry forest - Keila Rêgo Mendes; Willian Batista-Silva; Jaqueline Dias-Pereira; Marcos P. S. Pereira; Eliane V. Souza; José E. Serrão; João A. A. Granja; Eugênia C. Pereira; David J. Gallacher; Pedro R. Mutti; Duany T. C. da Silva; Rogério S. de Souza Júnior; et al. (Scientific Reports, 2022)
Abstract Plant species of the Brazilian Caatinga experience seasonal wet and dry extremes, requiring seasonally different leaf characteristics for optimizing water availability. We investigated if Croton blanchetianus Baill exhibits leaf morphoanatomical traits across seasons and positioning in sunlight/natural shade. Leaves of ten 1-3 m tall plants in full sunlight and ten in natural shade were assessed in May, July (wet season), October and December (dry season) 2015 for gas exchange, leaf size, lamina and midrib cross sections (14 parameters), and chloroplast structure (5 parameters). Net photosynthesis was greater during the wet season (21.6 µm−2 s−1) compared to the dry season (5.8 µm−2 s−1) and was strongly correlated with almost all measured parameters (p < 0.01). Shaded leaves in the wet season had higher specific leaf area (19.9 m2 kg−1 in full-sun and 23.1 m2 kg−1 in shade), but in the dry season they did not differ from those in full sun (7.5 m2 kg−1 and 7.2 m2 kg−1). In the wet season, the expansion of the adaxial epidermis and mesophyll lead to larger and thicker photosynthetic area of leaves. Furthermore, chloroplast thickness, length and area were also significantly larger in full sunlight (2.1 μm, 5.1 μm, 15.2 μm2; respectively) and shaded plants (2.0 μm, 5.2 μm, 14.8 μm2; respectively) during wetter months. Croton blanchetianus exhibits seasonal plasticity in leaf structure, presumably to optimize water use efficiency during seasons of water abundance and deficit. These results suggest that the species is adaptable to the increased drought stress projected by climate change scenarios.